Update breast cancer 2020 part 1- early breast cancer: consolidation of knowledge about known therapies = Update Mammakarzinom 2020 Teil 1 - frühes Mammakarzinom : Konsolidierung des Wissens über bekannte Therapien - Schneeweiss, Andreas; Hartkopf, Andreas D.; Müller, Volkmar; Wöckel, Achim; Lux, Michael P.; Janni, Wolfgang; Ettl, Johannes; Belleville, Erik; Huober, Jens; Thill, Marc; Fasching, Peter A.; Kolberg, Hans-Christian; et al. (Geburtshilfe und Frauenheilkunde, 2020)
This review is intended to present the latest developments in the prevention and treatment of early breast cancer. The risk of breast cancer can be increasingly better characterised with large epidemiological studies on genetic and non-genetic risk factors. Through new analyses, the evidence for high-penetrance genes as well as for low-penetrance genes was able to be improved. New data on denosumab and atezolizumab are available in the neoadjuvant situation as is a pooled appraisal of numerous studies on capecitabine in the curative situation. There is also an update to the overall survival data of pertuzumab in the adjuvant situation with a longer follow-up observation period. Finally, digital medicine is steadily finding its way into science. A recently conducted study on automated breast cancer detection using artificial intelligence establishes the basis for a future review in clinical studies.
Gesehen am 30.10.2020